Effect of interstitial impurities on internal friction measurements in niobium - Florencio, O.; Grandini, Carlos Roberto [UNESP]; Botta, FWJ; Guedes, P. R.; Silva, P. S. (Elsevier B.V., 2004)
Measurements of internal friction as a function of temperature were carried out in samples of mobium containing different amounts of interstitial solutes (oxygen and nitrogen) and one sample of mobium containing initially only nitrogen as interstitial solute. The experimental spectra of internal friction as a function of temperature were obtained with a torsion pendulum of the inverted Ke-type and resolved, using the method of successive subtraction, into a series of constituent Debye peaks corresponding to different interactions. For each relaxation process it was possible to obtain the height (Q(max)(-1)) and temperature (T-p) of the peak, the activation energy (E) and the relaxation time (t(o)). The height, shape and temperature of these peaks depend on the concentration of interstitial elements. The observed peaks were associated with matrix-interstitial (Nb-O, Nb-N) and interstitial-interstitial (O-N) interaction processes. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: points defect; niobium; internal friction